Analyzing The Relationship Between Mathematical Communication Skills, Learning Quality and Mathematics Learning Outcomes in Vocational High Schools - Majid Majid; Sry Selviana; Evi Hulukati; Franky Alfrits Oroh (STAI Hubbulwathan Duri, 2025)
Mathematics learning outcomes are essential indicators of educational goal achievement. However, many students, particularly in Grade X at SMK Tunas Harapan Bunobogu, Buol Regency, demonstrate low performance. Observations show that nearly 40% of students fall below the expected competency level, potentially due to limited interaction between internal and external learning factors. This study investigates the relationship between mathematical communication skills, learning quality, and mathematics learning outcomes. A quantitative correlational design was employed, involving 50 Grade X students selected through simple random sampling. Data were collected using validated questionnaires and mathematics achievement tests. Partial and multiple correlation analyses were conducted using IBM SPSS Statistics 27. Findings revealed a significant positive correlation between mathematical communication skills and mathematics learning outcomes, contributing 69.8% to the variance. Learning quality also showed a significant positive correlation, contributing 20.7%. When both variables were analyzed simultaneously, their combined influence on learning outcomes increased to 77.9%. These results suggest that both mathematical communication skills and learning quality play substantial roles in improving students' mathematics performance. Enhancing students' ability to express mathematical ideas, alongside improving instructional quality, could lead to better academic achievement. Future interventions should target both internal competencies and external instructional practices to optimize learning outcomes in vocational education contexts.